2003
DOI: 10.5713/ajas.2003.813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucosinolates of Taramira (Eruca Sativa) Oilcake on Nutrient Utilization and Growth of Crossbred Calves

Abstract: Taramira (Eruca sativa) cake, an unconventional oil cake, replaced 25 and 50 per cent crude protein of mustard cake in the ration of crossbred calves in an experiment of 90 days duration. Total glucosinolate content of the three concentrate mixture was almost similar (18.19, 17.95 and 17.95 µmol/g dry matter), however, glucouracin was the major glucosinolate of experimental diets. Similar dry matter Intake, nutrient digestibility (except those of fibre fractions) and nitrogen balances as well as similar serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…This is noteworthy because there is increased interest in GS for two reasons. Their degradation products demonstrate anticancer properties (Anilakumar et al, 2006;Brown et al, 2003;Das et al, 2003), and there is also potential for their use as biofumigants in pest control in conventional and organic production systems (Smolinska et al, 1997;Vaughn, 1997). If GS concentrations can be manipulated more easily by altering a limited number of genes, positive impacts on public health and the environment may result.…”
Section: Resultsmentioning
confidence: 99%
“…This is noteworthy because there is increased interest in GS for two reasons. Their degradation products demonstrate anticancer properties (Anilakumar et al, 2006;Brown et al, 2003;Das et al, 2003), and there is also potential for their use as biofumigants in pest control in conventional and organic production systems (Smolinska et al, 1997;Vaughn, 1997). If GS concentrations can be manipulated more easily by altering a limited number of genes, positive impacts on public health and the environment may result.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the replacement of 25 and 50% of mustard cake with ES oil cake in diets of crossbred calves had no significant effect on the digestibility of CP, CF, and EE. While, the digestibility of DM and OM were significantly increased only with 50% replacement (Das et al, 2003 ). Moreover, the digestibility of OM, CP, and NFE was not significantly influenced by replacing 50% of soybean meal with ES meal in rabbits’ diet (El-Tohamy and El-Kady, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of ES seeds addition in the present study, the improvement in ADG (numerically) and FCR ( P < 0.05) compared with control agrees with results obtained when ES seeds were added to the diets of rabbits (Fayed and Azoz, 2018 ). Furthermore, the inclusion of ES meal significantly enhanced ADG and FCR either of crossbred calves (Das et al, 2003 ) or rabbits (El-Nattat and El-Kady, 2007 ; El-Nomeary et al, 2015 ). In addition, El-Badawy et al ( 2018 ) reported that the addition of 1 or 2 mg ES oil/kg BW in diets of growing lambs improved ADG and FCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, glucosinolates are the major organoleptic and bioactive constituents of the Capparidaceae, Brassicaceae and a few other related plant families [ 10 , 11 ]. Glucosinolates compounds have long been known for their fungicidal, bactericidal, nematocidal and allelopathic properties, and have recently attracted attention researchers because of their cancer chemoprotective attributes [ 12 ]. Although, scientists highlighted the negative aspects of glucosinolate compounds because of the prevalence of certain “antinutritional” or goitrogenic glucosinolates degradation products, and ultimately affect the productivity of animals [ 13 ].…”
Section: Introductionmentioning
confidence: 99%